2010
DOI: 10.1093/annonc/mdq038
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy of advanced small-bowel adenocarcinoma: a multicenter AGEO study

Abstract: This is the largest study of chemotherapy in advanced SBA. Baseline PS and CEA and CA 19-9 levels were the main prognostic factors. FOLFOX seems to be the most effective platinum-based chemotherapy regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
158
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(170 citation statements)
references
References 32 publications
7
158
3
2
Order By: Relevance
“…9 The combination of 5-FU and a platinum-based agent has been considered more effective than other regimens such as oxaliplatinbased chemotherapy. 25,26 The main challenge for the near future is to identify molecular markers involved in small bowel carcinogenesis that predict chemosensitivity, and thus to improve survival. 5 Overman et al 27 observed that a high proportion of small intestinal adenocarcinomas express both EGFR and vascular endothelial growth factor (VEGF), suggesting that these patients may benefit from therapeutic strategies targeting EGFR and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…9 The combination of 5-FU and a platinum-based agent has been considered more effective than other regimens such as oxaliplatinbased chemotherapy. 25,26 The main challenge for the near future is to identify molecular markers involved in small bowel carcinogenesis that predict chemosensitivity, and thus to improve survival. 5 Overman et al 27 observed that a high proportion of small intestinal adenocarcinomas express both EGFR and vascular endothelial growth factor (VEGF), suggesting that these patients may benefit from therapeutic strategies targeting EGFR and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoropyrimidines are generally considered to be the key drugs for SBA and other gastrointestinal cancers. Most regimens used in previously reported studies of chemotherapy for unresectable SBA included fluoropyrimidines; to date, there has been no active regimen without these drugs [11][12][13][14][15][16][17][18][19][20][21][22][23]. However, no prospective or retrospective study has clearly showed advantages of a combination regimen compared with fluoropyrimidine monotherapy for unresectable SBA with regard to PFS or OS times.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted by AGEO compared oxaliplatin-and cisplatin-based chemotherapy. Although cisplatin (one of the key drugs for gastric cancer) was shown to be ineffective for colorectal cancer [24 -27], FOLFOX therapy (which includes oxaliplatin) was associated with significantly longer PFS and OS times in comparison with the combination of cisplatin and 5-FU for advanced SBA (4.8 vs. 6.9 months, p ϭ .02 for PFS; 17.8 vs. 9.3 months, p ϭ .04 for OS) [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations